Thermal analysis of a water source heat pump for space heating using an outdoor pool as a heat source. (January 2021) - Cardemil, J.M.; Schneider, W.; Behzad, M.; Starke, A.R.
Abstract: Water bodies are identified as potential heat sources (heat sink) for space heating (cooling) purposes. Thus, the nearby buildings can benefit from these sources by employing heat pump systems. This work presents a novel configuration of water source heat pump using outdoor pools in Mediterranean climate of Chile's central region for space heating. The annual transient performance of the system is modeled in TRNSYS using a physical deterministic model in combination with an equation-fitting procedure. The model accepts several parameters that represent the efficiency and size of the components of the system. Then the thermodynamics and economic performance matrices of the system are built as the output of the model. The results show the application of an outdoor swimming pool as a heat source is favorable without any serious situation of ice formation in the pool. In terms of different locations, the system operates more efficiently in a warmer climate, mainly due to lower required heat load and lower operating frequency. It is possible to reduce the operating time of the system considering a larger area of the pool, as well as higher nominal heating capacity, particularly for larger buildings. However, the analysis indicates that the system is economically feasible in buildings larger than 300 [m 2 ]. The proposed system can be installed in other places, sharing a similar climate zone and common building features. Highlights: TRNSYS simulation of Surface Water Heat Pumps for space heating. Outdoor swimming pool as a heat source for a heat pumps. Economic analysis considering heat pump and building features. Effect of climatic conditions in Mediterranean climates.